PENGARUH KOMPENSASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT TUNAS ANTARNUSA MUDA KARGO - Wiwik Rachmarwi; Niken Ayuningtyas (Jurnal Manajemen Bisnis Krisnadwipayana, 2024)
The purpose of this study was to determine the extent of the influence of employee compensation and work environment partially and simultaneously on employee performance. This study uses a quantitative approach. Data collection was carried out by distributing questionnaires to employees of PT Tunas Antarnusa Muda Kargo Jakarta. The analysis used in this study was descriptive analysis and multiple linear regression. The results of the study concluded that the compensation and the work environment have a significant influence partially and simultaneously on the employee performance.